Jojoba—Simmondsia chinensis (Link) S. - James M. Stephens (EDIS, 2003)
This document provides an overview of jojoba (Simmondsia chinensis), a desert shrub valued for its oil-rich nuts. Native to the Sonoran Desert, jojoba thrives in arid climates and is unlikely to flourish in Florida's humid conditions. The plant produces a unique, odorless oil used in cosmetics, lubricants, and other products. It is drought-resistant, long-lived, and adaptable to various soils. While not a traditional vegetable, its nuts have been consumed by Indigenous peoples and show potential for diverse applications, including food, animal feed, and ornamental use. Original publication date May 1994